2009
DOI: 10.1073/pnas.0907552106
|View full text |Cite
|
Sign up to set email alerts
|

A single Argonaute gene is required for induction of RNA silencing antiviral defense and promotes viral RNA recombination

Abstract: Dicer gene dcl2, required for the RNA silencing antiviral defense response in the chestnut blight fungus Cryphonectria parasitica, is inducible upon mycovirus infection and promotes viral RNA recombination. We now report that the antiviral defense response requires only one of the four C. parasitica Argonaute-like protein genes, agl2. The agl2 gene is required for the virus-induced increase in dcl2 transcript accumulation. Agl2 and dcl2 transcripts accumulated to much higher levels in response to hairpin RNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
198
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(207 citation statements)
references
References 38 publications
7
198
0
2
Order By: Relevance
“…Nuss and coworkers demonstrated that the RNA silencing components DCL-2 and AGL-2 are required for the generation of CHV1 DI-RNA species (27,28), and our previous study showed that the existing DI-RNA in EP155 rarely moved to the ⌬dcl-2 recipient side along with helper CHV1 in the lateral transmission assay (17). In the present study, we confirmed this with a virus mutant, CHV1-⌬p69, during RnVV1 coinfection assay in which DI-RNAs appeared only in the EP155 host backgrounds (see the asterisked DI-RNAs in Fig.…”
Section: W1029 Is Infected With a Novel Partitivirus And A Novel Victmentioning
confidence: 99%
See 3 more Smart Citations
“…Nuss and coworkers demonstrated that the RNA silencing components DCL-2 and AGL-2 are required for the generation of CHV1 DI-RNA species (27,28), and our previous study showed that the existing DI-RNA in EP155 rarely moved to the ⌬dcl-2 recipient side along with helper CHV1 in the lateral transmission assay (17). In the present study, we confirmed this with a virus mutant, CHV1-⌬p69, during RnVV1 coinfection assay in which DI-RNAs appeared only in the EP155 host backgrounds (see the asterisked DI-RNAs in Fig.…”
Section: W1029 Is Infected With a Novel Partitivirus And A Novel Victmentioning
confidence: 99%
“…It is known that CHV1 interferes with the host RNA silencing associated with the suppression of dcl-2 and agl-2 expression, possibly through the action of p29 of ORF A (26,27). We compared the levels of dcl-2 expression among EP155 colonies infected with different virus strains.…”
Section: Fig 8 Effects Of Vsr Expression On the Level Of Rnvv1 Replicmentioning
confidence: 99%
See 2 more Smart Citations
“…The function of ARGONAUTE (AGO) proteins is clearly essential since genetic inactivation of a single AGO without altering dicing enhances virus susceptibility in fungal, insect, nematode, and plant hosts (Li et al, 2002;Morel et al, 2002;Lu et al, 2005Lu et al, , 2009Schott et al, 2005;Wilkins et al, 2005;van Rij et al, 2006;Zambon et al, 2006;Qu et al, 2008;Sun et al, 2009). In Arabidopsis, hypomorphic ago1 and null ago7 mutants accumulate higher levels of viral RNA, and AGO1, AGO2, and AGO5 bind to viral siRNAs in the infected cells, suggesting an antiviral role for these AGOs (Morel et al, 2002;Zhang et al, 2006;Qu et al, 2008;Takeda et al, 2008;Azevedo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%